Pattern of superficial venous arrangement in cubital fossa among preclinical Nepalese MBBS students at Birat Medical College Teaching Hospital - Sah, Sanjib Kumar; Timsinha, Sidarth; Chaudhary, Raju Kumar; Shah, Rajesh Kumar; Mehta, Umesh Kumar (Asian Journal of Medical Sciences, 2021)
Background: The superficial veins of the cubital fossa are frequently variable in existence and arrangement. Many clinical procedures, such as reconstructive microsurgery and arterial bypass surgery, as well as intravenous injections or therapy, require the use of superficial veins.Aims and Objective: The aim of the study was to observe and describe the variations in anatomical distribution of the superficial veins of the cubital fossa in Nepalese pre-clinical medical students.Materials and Methods: The cross-sectional study included a total of 98 students between 18 to 24 years of age. A total of 196 anterior aspects of both arms were examined for cubital venous pattern. A tourniquet was applied at the mid-arm and drawing of the pattern of veins was made on a separate unglazed paper. The venous patterns in the cubital fossa were then categorized based on their gender.Results: Six patterns of superficial veins of the cubital fossa were observed. The commonest pattern in both genders was type I pattern. No statistical significant difference was observed between patterns of superficial veins on the right and left cubital fossa (P = 0.728 and 0.825 respectively) in both male and female subjects.Conclusion: Our research showed six venous patterns of superficial veins at the cubital fossa in Nepalese population. Understanding the common anatomy, patterns and variations of superficial vein anastomosis is imperative as this knowledge would help those needing venous access for various medical procedures.